Integration of Information Communication Technology Instructional Resources on Students' Motivation and Achievement in Chemistry Practical in Secondary Schools in Kenya - Munene, Titus Sifuna; Mutsotso, Stanley N.; Masibo, Edwin N. (Journal of Education and Practice, 2023)
Purpose: The main aim of this study was to determine the types of ICT instructional resources integrated and the level of motivation and achievement in learning of chemistry practical in secondary schools. Methodology: The study was conducted through descriptive survey design. The target population for this study were the teachers of chemistry, form three students and the heads of the institutions who were key informants. The schools were selected using stratified random sampling to ensure that there was equal representation of the region. The teachers of chemistry and ICT assistants were selected using simple random sampling technique while purposive sampling was used to select the heads of institutions. The learners were selected using simple random sampling. In the mixed secondary schools, stratified sampling technique was used to ensure gender equality. A sample is a smaller group selected from the target population; 34 teachers of chemistry were used in this study, 14 ICT assistants were used and 282 form three students in Bungoma County. This study used questionnaires as the main tool for collecting data. Work sheet was availed to the students for the experimental research; the work sheet contained simple questions in chemistry practical. The data collected was analyzed through descriptive and inferential analysis and the results were presented in tables and figures. Findings: The findings showed that majority of the schools that participated in the study have integrated ICT in teaching and learning of chemistry practical. The computers were available in the sampled schools and were accessible by teachers and form three students for integration in teaching of chemistry. The smart phones were also available but only teachers accessed these smart phones. The smart phones had the appropriate content that could be integrated in teaching chemistry practical. The media platform available in the smart phones could also allow teachers to project the content by use of overhead projectors and allow learners to view simulations and virtual chemical processes. Very few schools lacked the necessary infrastructure to handle ICT integration in teaching and learning of chemistry such as electrical installation and other fittings that could enable the projection of the content. There was no school in the study area that had the smart board which could allow teachers and learners to interact and manipulate the content to suit the needs for particular specific classes. Unique Contribution to theory, practice and policy: It was concluded that integration of ICT instructional resources could assist learners to perform some experiments in chemistry and provide better opportunities for teachers and students to interact with the content and with each other in the course of teaching and learning chemistry.